Device control and automation for neurocognitive and behavioral studies in experimental models - Pablo Capusso; Vanesa Roxana Sánchez (Revista Elektrón, 2022)
In recent years, the research in neuroscience and behavior fields has increased substantially. In this work, we design a device with an automatic control, detection and recording system of experimental tests to be used with experimental murine models for investigation. The technological solution developed allows the operation of the equipment to be associated with an interface that makes it easy for users to carry out experimental tests, analyze and monitor the results in a simple and efficient manner.